Analisis Kelayakan Usaha Street Food Untuk Pemanfaatan Lahan Parkir Pasar Modern - Putra, Rangga Herbowo; Chumaidiyah, Endang; Rendra, Meldi (JURNAL ILMU MANAJEMEN DAN BISNIS, 2019)
The street food area of Modern Market Goldland, Karawaci is an area that is provided for buying and selling activities among small and medium enterprises with consumers. Declining interest of the public to visit the shopping center as a result of their online shopping site makes one of the reasons why street food area began to develop, other than that street food festival can also help promote micro-economy of a country itself. This study aimed to determine whether land rental business street food is already feasible in terms of aspects of the market, technical, and financial aspects. Analysis of market aspects are used to determine potential markets, available markets and target markets. After collecting market data by distributing questionnaires, the potential market percentage is 94%, the available market is 97% of the potential market, and the target market is 5% of the available market. Analysis of technical aspects was carried out to see the outcome and income that occurred in the street food rental business in the next 5 years. The results of the calculation of financial aspects, obtained the value of NPV (Net Present Value) of Rp. 95,516,306, the value of IRR (Internal Rate of Return) of 27.67% and PBP (Pay Back Period) of 4.2 years. Because the IRR value is greater than the MARR value that is 11.74% and the NPV value is greater than 0, then the land leasing business by utilizing the street food market laha Modern Goldlan, Karawaci is said to be feasible.